Computational study of optical properties, and enantioselective synthesis of di-substituted esters of hydantoic and thiohydantoic acids - Hiwa Omer Ahmad (Zanco Journal of Pure and Applied Sciences, 2020)
The title compounds with different optically active substituted ester of hydantoic and thiohydantoic were synthesized by the reaction of corresponding enantio-pure amino acids methyl ester hydrochloride with phenylisocyanate/thiocyanate in the presence of triethylamine. The duration of reaction was limited to avoid racemisation and produce high enantio-enriched compounds. Low values of ELUMO-HOMO gap 0.14, 0.16, 0.15, 0.15, and 0.10 eV were observed for compounds 1, 2, 3, 4, and 5, respectively indicate soft, and high reactivity compounds. Values of ELUMO-HOMO gap also show that the compounds can easily decompose spontaneously to their elements. The order of synthesized compounds based on increasing reactivity depends on LUMO-HOMO energy gap represent as follows; 5>1>3, 4>2. Thermodynamic energies have been calculated for synthesized compounds including Enthalpy and Gibbs free energy.